Social work practice with men at risk - Furman, Rich (Columbia University Press)
Introduction -- Men's psychosocial health in a global era -- Conceptions of masculinity and the development of men -- The relationships of men -- Theoretical and practice guidelines -- Men and violence -- Workers at risk -- Warriors at risk -- The physical health of men -- Men and mental illness -- Older men at risk -- Diverse men at risk -- Men, compulsive disorders, and addictions -- Conclusion: what is right about men?